A internacionalização da educação superior no âmbito do Programa Idioma sem Fronteiras sob a perspectiva da política linguística - Silva, Bruno Maiorquino (2019)
The general objective of our research is to analyze the internationalization process of Brazilian higher education within the scope of the Languages Without Borders Program (LwB), characterizing it from the perspective of the Language Policy (LP) and focusing on the linguistic ideology on which it is based. To this end, we briefly follow the historical-epistemological development of LP and discuss specific concepts such as: the concept of language planning (COOPER, 1989); the multidimensional model of LP (SPOLSKY, 2004, 2009); the concept of linguistic mechanisms (SHOHAMY, 2006), and others . The research is interpretative in nature (MOORE; WILEY, 2015) and it is used as corpus the normative ordinances, published from 2012 to 2017, which establish the Program. In those we verified that LwBE can be described according to the “who plans what for who and how” categories of language planning as proposed by Cooper (1989), and that the linguistic ideology of internationalization at LwBE is driven by the belief in the potential for social and economic development provided by language qualification (especially in the English language due to its status as a lingua franca) and international academic mobility. In this sense, we highlight the role of extra linguistic factors linked to social and economic aspects that determine ideology, management and practices, thus interfering with linguistic behavior in society. The theoretical perspective and concepts in LP used in our work constitute an authentic and specific approach to the language policy of the internationalization of higher education and contributed to the research and implementation of public policies for foreign language teaching in our country.